AB1211 Utility of pet/ct for the diagnosis and disease manegement: a study of 88 patients from an autoimmune diseases hospital unit in a 2-year period. (12th June 2018) - Diéguez, P.; Argibay, A.; Vázquez Triñanes, C.; Gimena, B.; Estévez, M.; Lorenzo, R.; Val, N.; Freire, M.; Rivera, A.
Abstract : Background: 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F-FDG PET/CT) is a non-invasive imaging technique commonly used in clinical oncology. 18 F-FDG accumulation is recognised as useful for diagnosing and monitoring the response to therapy in patients with some inflammatory disorders, but the role of the PET/TC in the management of these diseases is debated. Objectives: The aim of this study was to investigate the role of 18F-FDG PET/CT in the diagnosis of the disease and assessing disease activity in an autoimmune diseases unit, and to evaluate if the results of this image technique imply a change in clinical management. Methods: We retrospectively reviewed all 18F-FDG PET/CT requested since August 2015 to August 2017 by our unit. Data collected were: patient demographics, reason for PET request, PET results and change in therapy. Results: PET/CT were performed in 88 patients and were positive in 68 (77, 3%) cases. Patients (49 women/39 men) had a mean age of 58, 1±15, 7 years (range, 27–92 years). The clinical diagnosis at the moment of ordering the PET/CT were: sarcoidosis (n=45), large-vessel vasculitis (LVV) (n=16), immunoglobulin G4-related disease (IgG4-RD) (n=9), collagen-vacular diseases (CVD) (n=7), mesenteric panniculitis (n=4), myopathy (n=4), polymyalgia rheumatica (PMR) (n=2) and ANCA-associated vasculitis (n=1). (See table 1 ). PET results supported a change in therapeutic management in 71.6% of the cases. In the group of sarcoidosis there was a change in treatment in 68.9% of cases. PET/TC revealed extrapulmonary manifestations in 57, 8%. All patients with extracranial manifestations of giant cell arteritis (GCA) showed uptake in PET/TC. That result supported the clinical diagnosis, although negative temporal artery biopsy. PET was useful in the diagnosis and treatment of IgG4-RD in 66, 7% of cases. PET scan did not find malignancy in inflammatory myopathies nor mesenteric panniculitis. Conclusions: PET/TC is an increasingly utilised in our patients with inflammatory disorders as a support for the diagnosis and management. PET/TC detection extrapulmonary sarcoidosis may have therapeutic and prognostic clinical implications. PET may be useful in patients with GCA supicion with negative biopsy and extracranial symptoms. More studies will be necessary to establish the real role of PET/TC in autoimmune and inflammatory diseases. Disclosure of Interest: None declared